The growth of Professional Master's programs in Pernambuco, Brazil (Research, Society and Development, 2021)
The current labor market demands have shifted education into new directions, requiring a specialized professional profile, in line with the modern demands of society. In this context, Professional Master's programs are presented as an option for providing the technical training required by the globalized labor market. The objective of the present study was to analyze the current state of Professional Master's programs in Pernambuco state, Brazil, in terms of the type of educational institution (public or private) and the main areas of knowledge, in addition to a temporal assessment of the evolution of these courses in terms of professional training. For this, information was retreived from the CAPES portal's electronic address, in addition to a bibliographic and documentary research. The results found show an increase in those programs in the last decade (2010-2020) in Pernambuco, accross all areas of knowledge, mainly in public Higher Education Institutions, revealing the importance of free professional qualification as essential for contemporary society.